High-efficiency visible-light photocatalytic H2O2 production using CdSe-based core/shell quantum dots. Issue 9 (30th March 2022) - Ji, Wenkai; Xu, Zaixiang; Zhang, Shijie; Li, Yang; Bao, Zhikang; Zhao, Zijiang; Xie, Liang; Zhong, Xing; Wei, Zhongzhe; Wang, Jianguo
Abstract : Quantum dots are demonstrated as photocatalysts for high-efficiency photocatalytic production of H2 O2 in a designed oil/water two-phase system. Abstract : Photocatalytic production of hydrogen peroxide (H2 O2 ) has received great attention as a promising route for sustainable solar fuel. In this work, we demonstrate that quantum dots (QDs) can be explored as a useful photocatalyst for high-efficiency photocatalytic production of H2 O2 under visible-light with a record-high concentration of 126 mmol L −1 . By band structure and wavefunction engineering, QDs exhibit an enhanced stability in an oxidized and humid environment. An oil/water two-phase system is designed to realize spontaneous separation of the H2 O2 formed to the aqueous phase and of the organic by-products formed to the oil phase. By electron paramagnetic resonance (EPR) measurements, ˙O2 − radicals are generated from QDs in the oil phase and transferred to the water phase immediately. The results in this work show that QDs with a rational surface and structure design can serve as an outstanding photocatalyst for the production of H2 O2 under visible-light.